2019
DOI: 10.1038/s41598-019-39116-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Changes in Response to Kinase Inhibitor H89 in PKA-Null Cells

Abstract: Protein phosphorylation, mediated by protein kinases, plays a crucial role in cellular regulation. One of the most important protein kinases is protein kinase A (PKA). N-[2-p-bromocinnamylamino-ethyl]-5-isoquinolinesulphonamide (H89) is often used as a “PKA specific inhibitor” to study the involvement of PKA in signaling pathways. However, evidence from cell-free experiments has suggested that H89 can also inhibit other protein kinases. In this study, previously generated PKA-null and PKA-intact mouse cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Almost all vasopressin‐mediated phosphorylation changes in murine immortalized cortical collecting duct (mpkCCD) cells were ablated when both PKA catalytic genes were deleted (PKA‐null cell) with CRISPR‐Cas9 genome editing (Datta et al, 2020). In addition, an inhibitor of PKA and other basophilic kinases, H‐89, blocked a large array of phosphorylation events in PKA‐intact mpkCCD cells that were not blocked in PKA‐null cells (Limbutara, Kelleher, Yang, Raghuram, & Knepper, 2019). Understanding of vasopressin signalling beyond PKA activation by cAMP remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all vasopressin‐mediated phosphorylation changes in murine immortalized cortical collecting duct (mpkCCD) cells were ablated when both PKA catalytic genes were deleted (PKA‐null cell) with CRISPR‐Cas9 genome editing (Datta et al, 2020). In addition, an inhibitor of PKA and other basophilic kinases, H‐89, blocked a large array of phosphorylation events in PKA‐intact mpkCCD cells that were not blocked in PKA‐null cells (Limbutara, Kelleher, Yang, Raghuram, & Knepper, 2019). Understanding of vasopressin signalling beyond PKA activation by cAMP remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were seeded in a 6-well plate at a density of 5 × 10 5 cells/well in MM. After 24 h, the cells were treated with or without glucagon in the presence or absence of 10 µmol/L H89, PKA inhibitor [ 46 ], in MM. After 30 min, the cells were incubated with a cell lysis buffer supplied by the manufacturer for another 30 min on ice with occasional vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…However, evidence from cell-free experiments has suggested that H89 can also inhibit other protein kinases (Davies et al, 2000). Limbutara et al (Limbutara et al, 2019) used PKA-null and PKAintact mouse cell lines derived from mpkCCD cells (see Section V) and quantitative phosphoproteomics to investigate the specificity of H89 over the range of concentrations commonly used in the literature. From a total of 14,507 phosphorylation sites quantified, the authors found that 578 phosphorylation sites were significantly changed in abundance in PKAintact and 267 sites were significantly changed in PKA-null cells.…”
Section: Effect Of Kinase Inhibitor H89 On Protein Phosphorylatimentioning
confidence: 99%